Faktor-Faktor Yang Berhubungan Dengan Angka Kuman Dalam Air Produk Air Minum Isi Ulang di Pemalang - Astuti, Sarwendah Dewi; Suhartono, Suhartono; Suwondo, Ari (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background: Safety of drinking water based on physical ,chemical,microbiological and radioactivity quality.A test of drinking water by Departement of Health in laboratorium of drinking water treatmen depot in Jakarta,indicaded Coliform bacteria contamination about 10%-20%.Its means occured contamination in several drinking water treatment depot. Methods: The aim of this research was to describe drinking water treatment process, and to analysis Coliform bacteria total after desinfection process in drinking water treatment depot. This research was an explanatory methods. Results: The population were all drinking water treatment depots in Pemalang District. Â Raw water used by drinking water treatment depot from well and artesian.The Physical treatment by screening and desinfection process used ozon, ultraviolet and the combination of ozon and ultraviolet. The result on laboratorium test showed that raw water was indicaded by positif Coliform bacteria.Water treated wais still found positive Coliform bacteria in several drinking water treatment depots. Data result from laboratorium test then was analyzed by statistics test, using Chi Square test,get p value = 0,009 less than alfa = 0,05.Its means Ho(nil hipotesis)was rejected.It means there were difference Coliform bacteria total after desinfection process in several drinking water treatment depots. Conclusion: To get drinking water with good quality, It must be maintenance on drinking water treatment process equipment continously. KeywordS : BacteriaL count, refill drinking water, Pemalang Regency